(3fXQjGJ hGSJQGJjLjGJ hfeGPL MOjKIs - (3CMeO(B, (3GdNWjHs; (3YGOd SGde eYGjYg(B, s ((3YeGf(B;(3GQHO(B,(3YGde GdcJH GdMOjK(B:s (3LOGQG ddcJGH GdYGdej ddfTQ h GdJhRjY(B,s, 2009)
(3GdGOGQI HGdKbI hGdJecjf, GOGQI GdeYQaI, GOGQI GdhbJ, GOGQI GdebGHdGJ, GOGQI aQjb GdYed, YedjI GJNGP GdbQGQGJ, GdGJUGd GdGOGQj, JbfjGJ MOjKI aj GdJWhjQ GdJfXjej, GOGQI GdUQGY GdJfXjejs
(3HHdjhZQGajG(B: (3U(B.515s
Keywords: (3GJNGP GdbQGQGJs; (3GdeYQaIs; (3GdeYdheGJs